-20p+4=4(-5p+1)

Simple and best practice solution for -20p+4=4(-5p+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20p+4=4(-5p+1) equation:


Simplifying
-20p + 4 = 4(-5p + 1)

Reorder the terms:
4 + -20p = 4(-5p + 1)

Reorder the terms:
4 + -20p = 4(1 + -5p)
4 + -20p = (1 * 4 + -5p * 4)
4 + -20p = (4 + -20p)

Add '-4' to each side of the equation.
4 + -4 + -20p = 4 + -4 + -20p

Combine like terms: 4 + -4 = 0
0 + -20p = 4 + -4 + -20p
-20p = 4 + -4 + -20p

Combine like terms: 4 + -4 = 0
-20p = 0 + -20p
-20p = -20p

Add '20p' to each side of the equation.
-20p + 20p = -20p + 20p

Combine like terms: -20p + 20p = 0
0 = -20p + 20p

Combine like terms: -20p + 20p = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| =4(2+4k)+(7k+1)8 | | =(ln(8*x+5))(x^4) | | D=(ln(8*x+5))(x^4) | | 6=-3t^2+36t | | -6(-10-15w)=5(18w+12) | | 2x^2+y^2+2xy-2x=-1 | | 3t^2-11t+6= | | 14v+7=-7(-2v-1) | | y=(ln(8*x+5))(x^4) | | =7(7+8k)+3(k+5) | | 17g+48=8(8g-11)-13g | | 3=(1/2)b+11 | | 2(-u-19)=-2+u | | 10=-16x^2+50x+30 | | 8t=-8(-t+13) | | -2(-6g-10)-5=-6g+15+18g | | -11p-20=-97 | | =(9k+1)6+(4+2k)9 | | -5-n=-11 | | (3/4)w-(1/2)(2w+1)= | | 40t=60t-30 | | -7.15-2.3u=-7.15-13u+10.7u | | 40-5x+5=-2x-10-4x | | 200-2p=3p-200 | | 13k+59+14k=5 | | 2.1h-3.91=2.78+2.1h | | 5x+2y=25 | | =9(7+k)+(6k+3)2 | | 4+v/10=5 | | 2g-1=11 | | 4r+7-6r+1=7r+9-3r-7 | | -9.7j+12.25=16j-8.31 |

Equations solver categories